2017
DOI: 10.1038/s41598-017-01114-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Brucella canis isolates using a highly discriminatory multilocus variable-number tandem-repeat analysis (MLVA) assay

Abstract: Differentiation of Brucella canis from other Brucella species are mainly performed through PCR-based methods and multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) procedures. Both PCR-based and MLVA methods are limited in discriminating B. canis strains. A new MLVA-13Bc method for B. canis genotyping was established by combining eight newly-developed VNTRs with five published ones. During 2010 and 2016, 377 B. canis PCR-positives were identified from 6,844 canine blood samples from 22 U.S. states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These findings indicate no obvious epidemiological relatedness among these strains and reveal that sporadic cases dominate the incidence of canine brucellosis in China. Previous studies have confirmed that MLVA‐16 genotyping results and epidemiological data are well correlated, with epidemiologically related isolates displaying identical or very closely related genotypes (Allen et al, ; Kilic et al, ; Yang et al, ). The seven genotypes were found in a total of 20 isolates, with each genotype represented by two to six isolates.…”
Section: Discussionmentioning
confidence: 74%
“…These findings indicate no obvious epidemiological relatedness among these strains and reveal that sporadic cases dominate the incidence of canine brucellosis in China. Previous studies have confirmed that MLVA‐16 genotyping results and epidemiological data are well correlated, with epidemiologically related isolates displaying identical or very closely related genotypes (Allen et al, ; Kilic et al, ; Yang et al, ). The seven genotypes were found in a total of 20 isolates, with each genotype represented by two to six isolates.…”
Section: Discussionmentioning
confidence: 74%
“…Besides the serological, biochemical and MALDI-TOF MS-based identification tools described above, molecular methods like ribotyping, pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST) or multiple locus variable number of tandem repeats (MLVA) analysis are used for subtyping of Brucella spp. 35 37 and for the differentiation of B. canis subclades 38 . As a consequence of the high genetic homology among Brucella species 39 , we performed next-generation sequencing (NGS) analyses for a more sophisticated phylogenetic characterization of the Brucella isolates in our study.…”
Section: Resultsmentioning
confidence: 99%
“…This was also true for the subset of sexually intact purebred adult dogs of breeding age (n = 1,397) identified as undergoing routine prebreeding serologic screening; 958 (68.6%) of these dogs were female and 439 (31.4%) were male. Investigators of a study 17 on B canis genotypes in samples submitted to the state veterinary diagnostic laboratory in Kansas also identified more samples from female (87/133 [65%]) than male dogs. Yet in the present study, 4 of the 7 dogs with diskospondylitis were males, 2 were females, and the sex of 1 was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…41 The variety of DNA extraction methods, primers, and amplification techniques used to detect B canis in dogs make direct comparisons among study results difficult. 17,40,41 At present, it appears that commonly used commercial kits for DNA extraction from canine blood samples are not, by themselves, sufficiently sensitive to recommend replacing blood culture for diagnosis of B canis in dogs. 40,41 Results depend on the quality of the sample submitted as well as the methodology used at the diagnostic laboratory and experience of personnel.…”
Section: Discussionmentioning
confidence: 99%